DUALISME PENGELOLAAN PENDIDIKAN ISLAM DI MADRASAH IBTIDAIYAH AL ISHLAH RANCAJAYA DAN SEKOLAH DASAR NEGERI KARYASARI 2 - Awin; Suparyati, Enok; Mutaqin, Mumu Zainal; Arifin, Muhammad (JURNAL KAJIAN ISLAM MODERN, 2025)
This study examines the dualism in the management of Islamic education at Madrasah Ibtidaiyah Al Ishlah Rancajaya and Sekolah Dasar Negeri Karyasari 2. The purpose of the research is to analyze the differences and similarities in managerial aspects, curriculum, and the implementation of Islamic education in both institutions. A qualitative descriptive approach was used, with data collected through interviews, observations, and document analysis. The findings indicate that the madrasah operates under the Ministry of Religious Affairs, integrating religious and general education in a balanced manner, while the public elementary school falls under the Ministry of Education and Culture, where Islamic education is limited to certain hours. This dualism affects students’ religious character development and the overall quality of their educational experience. Greater policy coordination between the ministries is necessary to establish equitable and high-quality Islamic education across all educational levels.